Investigation of the Electronic Structure of Transition Metal-Ions in Solution from Aqua-Complexes to Porphyrins - Golnak, Ronny (2017)
1 Introduction 1.1 Porphyrins Role in Nature 1.2 The Study of Solvated Porphyrins 1.3 Brief Introduction of the Thesis Content 2 Experimental and Theoretical Methods 2.1 X-ray Spectroscopies 2.1.1 X-ray Interaction with Matter 2.1.2 X-ray Absorption Coefficients and Cross-Sections 2.1.3 Radiative and Non-Radiative Decays 2.1.4 X-ray Absorption Spectroscopy (XAS) 2.1.5 X-ray Emission Spectroscopy (XES) 2.1.6 Resonant Photoelectron Spectroscopy (RPES) 2.2 Experimental Methods and Setups 2.2.1 Synchrotron Facility - BESSY II 2.2.2 Beamline - U41-PGM 2.2.3 Experimental Station - LiXEdrom 2.2.4 Liquid in Vacuum - Micro-Jet 2.2.5 Liquid in Vacuum - Flow Cell 2.3 Sample Preparation and Measurement Considerations 2.3.1 Aqueous Ferric Solution 2.3.2 Aqueous Ferrous Solution 2.3.3 FePPIX-Cl in DMSO 2.3.4 CoPPIX-Cl in DMSO 2.3.5 FePPIX- Cl in NaOH 2.3.6 MnOEP-Cl and MnTPP-Cl in DCM 2.3.7 FeOEP-Cl and FeTPP-Cl in DCM 2.4 Theoretical Modeling - ORCA Program Package 2.4.1 [Fe(H2O)6]3+ Complex 2.4.2 [Fe(H2O)6]2+ Complex (MOLCAS 8.0) 2.4.3 Porphyrin Complexes 3 Iron Chlorides in Aqueous Solution - a Simple Model System 3.1 Undistorted XAS Probed by Core-Level Emission 3.2 Metal-Ligand Interactions Revealed by Combined Probing of RIXS and RPES 4 Metalloporphyrins in Solution - a Complex System 4.1 Solvated Metalloporphyrin Monomers 4.1.1 FePPIX-Cl in DMSO 4.1.2 CoPPIX-Cl in DMSO 4.2 Intermolecular Interactions in FePPIX-Cl Dimer 4.2.1 Local Energy Gap Opening at the Iron Site 4.2.2 Characteristic XA-Feature Shifting of Nitrogen 4.3 Outer Ligand Effects on Metalloporphyrins in Solution 4.3.1 Outer Ligand Effect on the Metal Center 4.3.2 Metal-Solvent Interaction Assisted by Porphyrin Outer Ligands 5 Summary and Outlook This thesis reports how, by the development of the vacuum liquid micro-jet technique as well as the flow cell technique for soft X-ray spectroscopy, electronic structure measurements on liquid have advanced to date. My focus is on investigations of solvated transition metals in both simple and complex systems. ...